ARFs get the BioID treatment: what have we been missing?. (5th August 2022) - Barneda, David; Stephens, Len; Hawkins, Phillip
Abstract : Li et al present the results of a proximity‐interaction screen in mammalian cells for the effector proteins of 25 members of the Arf family of small GTPases. This study has generated an important resource for those working in several areas of cell biology and provided an initial characterisation of two new cellular roles for some of the least well studied members of this family, the regulation of PLD1 by ARL11/14 in phagocytosis, and the regulation of PI4KB by ARL5A/5B in the Golgi. Abstract : A proximity interaction screen of the human Arf family of small GTPases hints at a much larger functional range than anticipated.